Preventing persistent postsurgical pain: A systematic review and component network meta‐analysis. (8th February 2022) - Allen, Claire; Walker, Andrew M.; Premji, Zahra A.; Beauchemin‐Turcotte, Marie‐Eve; Wong, Jenny; Soh, Sonya; Hawboldt, Geoffrey S.; Shinkaruk, Kelly S.; Archer, David P.
Abstract: Background and objectives: Evidence for perioperative methods to prevent persistent postsurgical pain (PPP) is uncertain, in part because few treatments have been directly compared. Here we have used component network meta‐analysis (cNMA) to incorporate both direct and indirect evidence in the evaluation of the efficacy and tolerability of pharmacological and neural block treatments. Databases and data treatment: We searched the Cochrane Central Registry of Controlled Trials, Embase, MEDLINE, ClinicalTrials.gov and the World Health Organization International Clinical Trials Registry up to January 2021 for randomized, double‐masked, controlled trials that reported the prevalence of PPP. We assessed trial quality with the Cochrane risk of bias tool (RoB 2.0). We analysed the results with frequentist cNMA models. The primary outcome was the relative risk (RR) of PPP. We assessed efficacy in relation to a clinically important effect size of RR = 0.9, which is a 10% improvement with treatment. Results: The analysis included 107 trials (13, 553 participants) of 13 treatments. The effects of complex interventions were the multiplicative effects of their components. Compared with placebo, serotonin–norepinephrine reuptake inhibitors (SNRIs), neural block alone, or in combination with NMDA receptor blockers or gabapentanoids were effective. Treatments with benefit in the immediate post‐operative period predicted a reduced risk of PPP. Conclusions: Several treatments and treatment combinations effectively reduce PPP prevalence. Pain outcomes in the immediate postoperative period are an important mediator of PPP. Multimodal interventions can be analysed using cNMA. Significance: Systematic reviews of PPP prevention usually focus on the efficacy of specific treatments in comparison with control interventions. In this study we used component network meta‐analysis to compare interventions to each other, including both pharmacological and neural block techniques, and multimodal interventions. Interventions that are not effective alone may improve the efficacy of multimodal interventions that include neural block techniques. Immediate postoperative benefit was an important mediator for reduction of PPP. Study registration: PROSPERO: CRD42018085570 https://www.crd.york.ac.uk/prospero/ .